Rare diseases: ethical challenges in the era of digital health - Liesbeth Siderius; Liesbeth Siderius; Sahan Damsiri Perera; Lina Jankauskaite; Lina Jankauskaite; Anjan Bhattacharya; Anjan Bhattacharya; Paulo Gonçalves (Frontiers in Digital Health, 2025)
To improve the health and wellbeing outcomes of people with rare conditions, it is necessary to integrate all aspects of health and wellbeing. Digital health technologies can appropriately capture and share harmonised data between care providers and the individuals concerned. The quality of digital health is dependent on defined data points reflecting the actual medical and societal situation and register changes when new diagnostics or therapies become available. The life experiences of individuals living with a condition, individually or as a group, are underrepresented in the digitalising world. This narrative review addresses rare conditions as an entity, public health strategies, digital health opportunities, and ethical considerations. The challenge is illustrated by comparing data gathered by manually selected data points with advanced artificial intelligence systems. In this new digital era, we consider the philosopher Kant's notion of noumena: “Only individuals with rare disabling conditions can genuinely convey the reality of living with those conditions”. In conclusion, there is a pressing demand to embed the needs and experiences of people in all new technologies.